Convenient syntheses of orthogonally protected aminocyclopentitols from aldopentoses. Issue 3 (14th January 2015) - Košak, Urban; Hrast, Martina; Knez, Damijan; Maraš, Nenad; Črnugelj, Martin; Gobec, Stanislav
Graphical abstract: Abstract: Orthogonally protected aminocyclopentitols were synthesized from commercially available aldopentoses using a convenient three-step procedure that does not require protection of the free anomeric hydroxyl group of the starting carbohydrate. The synthesized compounds are important building blocks with potential use in medicinal chemistry and drug discovery.